Mechanisms of extracellular vesicle-mediated immune evasion in melanoma - Dieterich, Lothar C. (Frontiers in Immunology, 2022)
Melanoma-derived extracellular vesicles (EVs) have been found to promote tumor growth and progression, and to predict patient responsiveness to immunotherapy. Consequently, EVs have been implicated in tumor immune evasion, and multiple studies reported immune-regulatory activities of melanoma EVs in vitro and in vivo. This review highlights mechanistic insights in EV-mediated regulation of various immune cell types, including effects on inflammatory, apoptotic, stress-sensing and immune checkpoint pathways as well as antigen-dependent responses. Additionally, current challenges in the field are discussed that need to be overcome to determine the clinical relevance of these various mechanisms and to develop corresponding therapeutic approaches to promote tumor immunity and immunotherapy responsiveness in melanoma patients in the future.